STUDI PENCAMPURAN BATUBARA KUALIATAS RENDAH DENGAN ARANG GERGAJI KAYU SENGON PADA PROSES PEMBUATAN BRIKET - Donal; Harjuni Hasan; Agus Winarno; Windhu Nugroho; Shalaho Dina Devy (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
Abstract: Abstract: This research aimed to discover the percentage of the proximate analysis results in the coal and to discover its effect on the calorific value of the coal it was conducted by obtaining the coal samples to be analyzed, and the samples were then processed to produce the samples ready to testing. The results have shown that variations of adhesive had a significant effect on moisture, ash content, volatile matter, fixed carbon, temperature of combustions while not affected the rate and density and compressive strength. The best treatment from this study was obtained from treatment charcoal and with compostions 50% coal : 50 sengon charcoal with sampel code KH (pulaubalang) and resulting from this treatment briquettes were moisture of 5.99 % ; ash content 6,92 % ; volatile matter 11,42% fixed carbon 75,65% burning rate of 3,74 g/minute; fire ignition 6: 36 minute; density of 0,23 g/cm3; compressive strength of 38,22 kg/cm2. Briquets with composition 50% coal : 50 sengon charcoal with sampel code KP (balikpapan) and resulting from this treatment briquettes were moisture of 6,96 % ; ashcontent 4,73 % ; volatile matter 11,92% fixed carbon 76,39% burning rate of 2,61 g/minute; fire ignition 6: 57 minute; density of 0,21 g/cm3; compressive strength of 24,70 kg/cm2.